Coquasi – Invertible Submodule - Naoum, Adil; Al-Hashimi, Basil; Yaseen, Sahera (Iraqi Journal of Science, 2025)
Let R be a commutative ring with identity. We call the proper submodule N ofM a coquasi - invertible submodule if (M, N)  0Hom(M,N)  0Hom the main purpose of thiswork is the study of the properties of coquasi - invertible submodules. and givedefinithon of corational submodule. Then show that if M is self projective, then Nis coquasi - invertible submodule of M if and only if N is corational in M